Microvascular Ultrasonography Vascularity Index as a Rapid and Simplified Assessment Tool for Differentiating Graves’ Disease from Destructive Thyroiditis and Managing Thyrotoxicosis - Han-Sang Baek; Chaiho Jeong; Jeonghoon Ha; Dong-Jun Lim (Endocrinology and Metabolism)
Background Thyrotoxicosis presents significant diagnostic challenges in distinguishing Graves’ disease (GD) from destruction-induced thyrotoxicosis (DT) using ultrasound imaging. We evaluated a new technology, microvascular ultrasonography (MVUS) to effectively differentiate between GD and DT, and observe the MVUS changes during follow-up. Methods A total of 264 consecutive patients were prospectively enrolled into two cohorts from August 2022 to March 2024 at one tertiary referral hospital: cohort 1 comprised patients initially presenting with thyrotoxicosis (n=185; 98 with GD and 87 with DT). Cohort 2 included patients either with GD considering antithyroid drug discontinuation or with DT in the follow-up phase after treatment (n=77). Ultrasound imaging was conducted using the MVUS technique, and the vascularity index (MVUS-VI) was automatically calculated as the percentage ratio of color pixels to total grayscale pixels within a specified region of interest. Results Diagnostic accuracy highlighted MVUS-VI as the most accurate diagnostic tool, achieving a sensitivity of 79.6%, specificity of 84.3%, with an area under the curve of 0.856 (95% confidence interval, 0.800 to 0.911). Presence of thyroid peroxidase antibody or thyroglobulin antibody affected MVUS-VI’s performance, requiring a higher cut-off value for specificity in this subgroup. Follow-up in cohort 2 (n=77) demonstrated significant normalization in thyroid function and reductions in MVUS-VI from an initial 32.6%±23.4% to 20.8%±13.5% at follow-up (P<0.001). Conclusion MVUS-VI provides a rapid, non-invasive diagnostic alternative to traditional methods in differentiating GD from DT, thus aiding in the management of patients with thyrotoxicosis.